Educating future medical professionals with the fundamentals of law and ethics - Jahn Kassim, Puteri Nemie; Osman, Ariff; Wan Muhammad, Ramizah (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
The increasing awareness amongst the society on medico-legal issues as well as the growth of consumerist attitude towards the provision of medical services has caused the medical profession to be subjected to vociferous criticism if they do not meet rising expectations of the society. Substandard services have not been well tolerated and paternalistic approaches in medical treatment are considered to be outmoded and inappropriate. Any dissatisfaction on the part of the patient towards medical services provided nowadays may easily trigger claims in the court of law. This changing trend has also fundamentally changed the behaviour of the courts towards the medical profession. Judicial and legislative interventions in medical practice have created more and more rights for the patients and consequently, corresponding legal duties for the medical profession to uphold. In the present healthcare setting, the medical profession will not be able to provide infallible services without knowledge of the legal standards which they have to adhere. Thus, educating future medical professionals with the fundamentals of law and ethics would ensure greater accountability, knowledge and personal commitment in providing medical services to the society as the ideals of professionalism not only require them to have the necessary expertise, dedication, respect, compassion, empathy, honesty, altruism, responsibility, integrity, self-improvement and accountability but also adherence to the demands of law and highest ethical standards.